DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS X MAN KOTA SOLOK - Haniva Aini; Budi Juliardi; Azwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the impact of TikTok social media use on students' learning motivation in the Pancasila Education subject among tenth-grade students at MAN Kota Solok. This research employed a quantitative approach using an ex post facto design. The population consisted of 208 students, while 52 students were selected as the sample through simple random sampling. Data were collected using a questionnaire and analyzed through descriptive statistics, normality testing, simple linear regression, the coefficient of determination, and the t-test using SPSS version 22. The findings revealed that TikTok social media use has a positive and significant effect on students' learning motivation, as indicated by a significance value of 0.016 (<0.05) and a regression coefficient of 0.426. The coefficient of determination was 11%, indicating that TikTok use contributed to students' learning motivation, while the remaining 89% was influenced by other factors beyond the scope of this study. Therefore, the appropriate and educational use of TikTok can serve as a supporting medium for enhancing students' learning motivation in Pancasila Education.